STRATEGI PENINGKATAN KOMPETENSI GURU DALAM PENERAPAN PAKEM MELALUI KEGIATAN PELATIHAN DAN BIMBINGAN DI SMAN 1 PEUKAN PIDIE - Musliadi Musliadi (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
This School Action Research was conducted against the background of low student learning outcomes. Observations show that only a small proportion of SMAN 1 Peukan Pidie teachers have implemented an active, creative, effective, and fun learning approach (PAKEM) in learning. The purpose of this study was to improve the competence of teachers at SMAN 1 Peukan Pidie. The formulation of the research problem is: How is the effectiveness of the training and guidance activities carried out by the principal on increasing teacher competence in the application of active, creative, effective, and fun learning (PAKEM) at SMAN 1 Peukan Pidie?. The research was conducted with an action research approach through three cycles. The results of the study concluded that (1) training in the form of workshops and guidance on the application of the PAKEM approach had increased the understanding (insight) and skills of SMAN 1 Peukan Pidie teachers about the importance of implementing the PAKEM approach in classroom learning; (2) The results of the analysis show that training activities in the form of workshops provide more knowledge for teachers about the workshop material itself, in this case the PAKEM approach, while the increase in teacher skills in implementing PAKEM in the classroom is mostly obtained through guidance activities in direct practice; and (3) Based on the results of the reflection, it is known that the competence of teachers increases through training and guidance on the application of PAKEM in learning.Keywords: Competence, PAKEM, Training, Guidance